ANALISIS PERBEDAAN KINERJA BANK UMUM SYARIAH DAN BANK UMUM KONVENSIONAL DI INDONESIA - Ni Kadek Sri Budiartini; Anak Agung Putu Agung; Agus Wahyudi Salasa Gama (Forum Manajemen STIMI Handayani Denpasar, 2017)
This study aims to compare the financial performance of Sharia Commercial Banks with Conventional Banks in Indonesia in the period 2010-2015 using financial ratios. The financial ratios used consist of CAR, KAP, PPAP, NPM, ROA, BOPO, and LDR. The data used in this research is obtained from Bank Finance Publication Report 2010 to 2015 issued by Indonesia Stock Exchange. After passing through the purposive sample stage, then a decent sample is used as many as 12 samples, 6 Sharia Commercial Banks. The analytical technique used to compare the financial performance of Sharia Commercial Bank with Conventional Bank is the Independent sample t-test and Mann Whitney Test method. The analysis shows that there are significant differences for each financial ratio between Sharia Commercial Bank and Conventional Bank in Indonesia. Sharia Commercial Bank performs better in terms of CAR and KAP ratios, while Conventional Commercial Banks perform better in terms of ratio of PPAP, NPM, ROA, BOPO, and LDR.